Nature As A Subject Of Rights In The Sanctioning Procedure In The Organic Environmental Code. Ecuador - Mendoza Escalante, Pablo Ricardo; Mendoza Rojas, Isabel Alejandra (Ius Humani. Jornal do direito, 2024)
Research on the rights of nature in the field of administrative procedural law constitutes a new challenge based on the sanctioning power of the Ecuadorian State within the sanctioning procedure provided for in the Organic Code of the environment in Ecuador. Accordingly, the research addressed, from the new conception of nature as a new subject of rights, the role of the subject interested in the results of the sanctioning procedure provided for in the CODA. In this context, aspects such as the status of procedural subject, legitimation, jurisdiction, due process, the natural judge, evidence, the sentence and its necessary motivation were addressed, through legal argumentation. A legal dogmatic documentary type methodology was used, which allowed the analysis of the different legal institutions in the constitutional resolutions in administrative matters, as well as the regulations linked to the application of a procedure arising from the sanctioning power for environmental administrative infractions from the legal framework. the doctrine and jurisprudence of the Constitutional Court. It was concluded that although the principles of Criminal Law are applicable, they must be interpreted and applied based on the guiding principles of environmental law and the rights recognized in article 71 of the 2008 constitution. It has not been possible to delve deeper into decentralized environmental management. and on the rights of nature within the administrative sanctioning procedures in the Ecuadorian legal system in relation to the constitutive elements of the rights of respect and restoration of nature.